PROTECTION OF CHERNOBYL AREA CULTURAL HERITAGE: BELARUSIAN MUSEUMS’ EXPE RIENCE - Kovalev, Evgeny А. (Acta Museologica Lithuanica, 2015)
An article contains information on the Belarusian museums activities which aims at the preservation of cultural heritage at the areas abandoned after the Chernobyl accident. The author presents his findings on the implications of the Chernobyl disaster for historical and cultural heritage of Belarus. The histories of expeditions undertaken in the polluted area, the character of survived objects and forms of their presentation at museum exhibitions are presented in the article. The author pays his attention to the problem of the affected area intangible heritage preservation as well. The Belarusian higher educational institutions which are engaged in the preservation of intangible heritage of abandoned area are shown as the important partners of the museums in the field.
Keywords: The Chernobyl accident; Chernobyl area; cultural heritage; Eastern Polesye; state museums; ethnography